2013
DOI: 10.1097/olq.0b013e31827adc06
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Intention to Seek Medical Care After Hypothetical Receipt of Patient-Delivered Partner Therapy or Electronic Partner Notification Postcards Among Men Who Have Sex With Men

Abstract: Although many MSM express interest in using PDPT and anonymous e-cards, these methods may result in missed opportunities to test for HIV and other STDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The lack of an observed effect on downstream outcomes indicates the need for additional interventions to support partner management outcomes throughout the partner management cascade, beginning with notification, and culminating with linkage to and retention in HIV/STI care (45). While preliminary research on potential responses to hypothetical anonymous notification messages among MSM in Peru indicated that recipients would be motivated to seek medical attention after receiving an anonymous message, data from the U.S. has suggested the opposite, and our study did not collect any partner-confirmed information on post-notification behavior (30,46).…”
Section: Discussionmentioning
confidence: 63%
“…The lack of an observed effect on downstream outcomes indicates the need for additional interventions to support partner management outcomes throughout the partner management cascade, beginning with notification, and culminating with linkage to and retention in HIV/STI care (45). While preliminary research on potential responses to hypothetical anonymous notification messages among MSM in Peru indicated that recipients would be motivated to seek medical attention after receiving an anonymous message, data from the U.S. has suggested the opposite, and our study did not collect any partner-confirmed information on post-notification behavior (30,46).…”
Section: Discussionmentioning
confidence: 63%
“…We identified one study that assessed the acceptability of receiving an e-card notification of exposure to an STI (Kerani, Fleming, & Golden, 2013). In this study men were asked “If you received an anonymous e-mail card saying that you might have been exposed to gonorrhea or chlamydia by a sex partner, would you go get tested?” Individuals were asked the same question regarding a partner telling them of the exposure face to face.…”
Section: Resultsmentioning
confidence: 99%
“…One in three STI clinic patients have been found to be likely to use the phone to notify their partners of an STI (Rietmeijer et al, 2011). Another study found that 56% of MSM would be more likely to respond proactively if they received a phone message from a sex partner relative to anonymous e-cards (Kerani et al, 2013). When multiple options were presented from which patients could choose, 62% of patients preferred notifying partners by phone compared to 53% who preferred in person, 45% who preferred e-mail, and 39% who preferred anonymous e-cards.…”
Section: Resultsmentioning
confidence: 99%
“…4 Other methods involve anonymous notification via email, text messaging or electronic postcards (e-cards). 5 These electronic methods are sometimes provider-initiated and other times patient-initiated through Internet applications. Some of these methods have only recently been put into practice.…”
Section: Introductionmentioning
confidence: 99%